A Systematic Literature Review: The Effectiveness of Vocabulary Size Tests on Students English Vocabulary and Writing Skills - Nitami, Kadek Dian; Santosa, Made Hery (LETS: Journal of Linguistics and English Teaching Studies, 2024)
This research aims to examine the benefits of integrating vocabulary size test in the context of learning English learners as well as the relationship between vocabulary and writing skills. Using the systematic literature review (SLR) method, this research analyzed 18 selected articles published between 2019-2024. The results of the research show that the web-based vocabulary measurement is proven to be effective and efficient in measuring the Vocabulary of English students. Its advantages include accessibility, time efficiency and ease of use. In addition, a strong positive correlation was found between vocabulary and students' writing skills at various levels of education. The integration of this technology not only increases student learning motivation but also has the potential to strengthen students’ writing skills. In conclusion, developing a vocabulary size test website is an important strategy in modern English language learning since it facilitates increased mastery of vocabulary which ultimately supports the development of students' writing skills.